PENGARUH FASILITAS BERMAIN ANAK SEBAGAI STRATEGI PELAYANAN BAGI KEPUASAN KONSUMEN - Novy Anggraini; Rusmala Dewi (KOLEGIAL, 2018)
To attract consumers and keep them in order to survive and continue to grow, PT Thamrin Brothers Branch Baturaja 2 presents a playground for children in their workshop. The purpose of this study is to see how big the influence placement of children playground in improving consumer satisfaction so that service to the consumer is fulfilled. The research method used is descriptive research method with data source come from primary data and secondary data. Primary data obtained from questionnaires filled with respondents. Data analysis techniques used are simple linear regression analysis, simple linear correlation analysis, a coefficient of determination, and hypothesis testing. The result of the analysis shows that there is strong influence between the variable of children playground with the variable of consumer satisfaction. This means that if the playground of children increases then the satisfaction of consumers will also experience an increase. Thus, the decision to placement children playground as a service strategy to consumers of workshops conducted by PT Thamrin Brothers Branch Baturaja 2 is appropriate because it affects the increase in sales and consumer confidence so that consumers feel satisfied and feel the company is able to meet their needs when consumers visit company workshop.